Tulsa Race Riots and the Red Summer of 1919 - Winn, Kevin P.; Wing, Kelisa (Racial justice in America: histories., 2022)
Introduces readers to the racial violence that erupted across the U.S. during the summer of 1919, and to the Tulsa race riots of 1921. Includes photographs, profiles, sidebars, critical-thinking questions, activities, a glossary, and additional resources.